ANALISIS TINGKAT EFEKTIVITAS PAJAK KENDARAAN BERMOTOR DAN KONTRIBUSI PADA PAJAK DAERAH DI KABUPATEN BERAU - Henika Febrianti Putri (ECO-BUILD, 2025)
This study has three main objectives: (i) to determine the effectiveness of PKB receipts in 2019, 2020, and 2021; and (ii) to find out the contribution made by PKB to the Berau Regency Regional Tax in 2019, 2020, and 2021. (iii) PKB Growth Rate for Regional Taxes in Berau Regency in 2019, 2020, and 2021. This research was conducted at the BAPENDA Office located at Jl. Dr. Murjani I No. 86, Berau Regency with PKB admission data for the 2019, 2020, and 2021 periods. This study studies data on the realization of targets and the realization of tax revenues at the Berau Regency Regional Revenue Agency in 2019-2021. From this data, the author can calculate and analyze the ratio of motor vehicle tax effectiveness, motor vehicle tax contribution, and growth in motor vehicle tax revenue. Based on the results of the research conducted, the researcher concluded that the effectiveness of PKB receipts has been very effective because it exceeds 100%, namely 120% in 2019, 114% in 2020, and 101% in 2021. In addition, the researcher concluded that the contribution made by PKB to Regional Taxes has been very good because it exceeded 50%, namely 81% in 2019, 75% in 2020, and 70% in 2021. The growth rate in 2020 was -0.11%, decreasing, in 2021 there was an increase of 0.08%.